Apaf-1 is an evolutionarily conserved DNA sensor that switches the cell fate between apoptosis and inflammation - Jie Ruan; Xuxia Wei; Suizhi Li; Zijian Ye; Linyi Hu; Ru Zhuang; Yange Cao; Shaozhou Wang; Shengpeng Wu; Dezhi Peng; Shangwu Chen; Shaochun Yuan; et al. (Cell Discovery)
Abstract Apoptotic protease activating factor 1 (Apaf-1) was traditionally defined as a scaffold protein in mammalian cells for assembling a caspase activation platform known as the ‘apoptosome’ after its binding to cytochrome c. Although Apaf-1 structurally resembles animal NOD-like receptor (NLR) and plant resistance (R) proteins, whether it is directly involved in innate immunity is still largely unknown. Here, we found that Apaf-1-like molecules from lancelets, fruit flies, mice, and humans have conserved DNA sensing functionality. Mechanistically, mammalian Apaf-1 recruits receptor-interacting protein 2 (RIP2, also known as RIPK2) via its WD40 repeat domain and promotes RIP2 oligomerization to initiate NF-κB-driven inflammation upon cytoplasmic DNA recognition. Furthermore, DNA binding of Apaf-1 determines cell fate by switching the cellular processes between intrinsic stimuli-activated apoptosis and inflammation. These findings suggest that Apaf-1 is an evolutionarily conserved DNA sensor and may serve as a cell fate checkpoint, which determines whether cells initiate inflammation or undergo apoptosis by distinct ligand binding.